Alterations of adiponectin in the course of inflammation and severe sepsis - Behnes, Michael; Brückmann, Martina; Lang, Siegfried; Saur, Joachim; Borggrefe, Martin; Hoffmann, Ursula (Shock, 2012)
ABSTRACT The adipocyte-specific protein adiponectin reveals anti-inflammatory, antioxidant, antiatherosclerotic and vasoprotective effects. This study aims to investigate adiponectin expression in cultured human adipocytes within an inflammatory model and in patients with severe sepsis and evaluates treatment effects of drotrecogin α (activated) (DAA). In an in vitro inflammatory model of adipocyte cell culture, the effect of DAA on adiponectin mRNA expression was evaluated. Synthesis of mRNA was measured by quantitative polymerase chain reaction. Supernatants of these adipocytes and serum levels of adiponectin were measured in blood of 104 patients by enzyme-linked immunosorbent assay on days 1, 3, and 5 of severe sepsis. Twenty-six patients were treated with DAA (DAA+), 78 patients without DAA (DAA−). Stimulation of human adipocytes with tumor necrosis factor α over 6 and 24 h resulted in a significant decrease in adiponectin mRNA transcripts. After 24 h of incubation, adiponectin mRNA expression was significantly upregulated according to applied dosages of DAA at 50 ng/mL and 5 μg/mL (P < 0.05). Accordingly, adiponectin levels of supernatants of adipocyte culture increased after 24 h (P < 0.05). DAA− patients revealed significantly higher adiponectin serum levels compared with healthy controls (P < 0.1) and DAA+ patients (P < 0.05) at days 1 and 3. On day 5 after 96-h infusion of DAA (24 μg/kg per hour), adiponectin levels significantly increased in DAA+ patients and equalized toward DAA− patients (P > 0.1). Adiponectin might be involved in the pathogenesis of the systemic inflammatory response during sepsis. Administration of DAA upregulates adiponectin expression under circumstances of systemic inflammation.
Gesehen am 26.10.2018